2007
DOI: 10.1093/sleep/30.10.1309
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-Disordered Breathing and Psychomotor Vigilance in a Community-Based Sample

Abstract: , LEADING TO nocturnal arousals, unrefreshing sleep, and daytime sleepiness. SDB has been shown to be a contributing factor in diminished neurocognitive functioning. [1][2][3][4] Specifically, within the spectrum of neurocognitive deficits, vigilance impairment or inability to sustain attention is a frequent complaint of patients with SDB. Vigilance lapses have been shown to be associated with sleepiness-regardless of the cause-as well as with fatigue and alcohol impairment, 5-7 and the lapses have been found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
71
3
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 38 publications
8
71
3
1
Order By: Relevance
“…The mean reaction time on the PVT was 315.0 (+65.1) with 90% of subjects demonstrating reaction times exceeding the 19 The mean number of lapses was 3.98 (+5.24) with 59% exceeding the mean (1.96) for an age-and sex-matched control (p=0.001). 19 The Figure, a scatter plot of MFIS score against PVT reaction time, demonstrates the correlation between reaction times and fatigue scores.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…The mean reaction time on the PVT was 315.0 (+65.1) with 90% of subjects demonstrating reaction times exceeding the 19 The mean number of lapses was 3.98 (+5.24) with 59% exceeding the mean (1.96) for an age-and sex-matched control (p=0.001). 19 The Figure, a scatter plot of MFIS score against PVT reaction time, demonstrates the correlation between reaction times and fatigue scores.…”
Section: Resultsmentioning
confidence: 92%
“…For example, in other studies age has been shown to affect PVT performance, and in this study, gender was a significant contributor. 19 However, these observations also illustrate the drawback of traditional fatigue rating scales, which encompass several distinct parameters -short-term attention, exercise tolerance, sustained concentration capabilities -under the umbrella of fatigue. Perhaps it will be fruitful in the future to research MS fatigue by differentiating this entity into several, smaller, objectively defined components, including alertness.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations